Book Review-Stepping Up: Lead Culture Change for Diversity and Growth in the Asian Century. - P. Young (The journal of contemporary issues in business and government, 2014)
The call for greater diversity in our workplaces has swelled across Australian managerial and public policy contexts since the early 1990s. Despite the seeming popularity of diversity, representation of women and racial minorities in positions of leadership remains abysmally low. In Stepping Up, Pamela Young boldly points out the social inequalities that hinder the progression of certain people in business and society. The book is written for leaders and presents the voices of 100 of their peers, predominantly those working in Australia or from Australia working in Asia.